2008
DOI: 10.1007/s00425-008-0854-6
|View full text |Cite
|
Sign up to set email alerts
|

BREVIS RADIX is involved in cytokinin-mediated inhibition of lateral root initiation in Arabidopsis

Abstract: In contrast to auxin, relatively little is known about the molecular mechanism of cytokinin (CTK) inhibition of lateral root initiation. Previous studies demonstrated that BREVIS RADIX (BRX), a protein of unknown biochemical function, maintains a rate-limiting brassinosteroid biosynthesis enzyme expression to keep brassinosteroid biosynthesis above a critical threshold. Here, we show that the brx-2 mutant is insensitive to exogenous CTK-induced inhibition of lateral root initiation and that this can be restore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…Exogenous CK application reduces PR elongation and represses the initiation of LRs in wild-type Arabidopsis (Li et al, 2009). We observed some sensitivity of the arm mutant toward exogenous CK application, but the wild type was affected as well (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Exogenous CK application reduces PR elongation and represses the initiation of LRs in wild-type Arabidopsis (Li et al, 2009). We observed some sensitivity of the arm mutant toward exogenous CK application, but the wild type was affected as well (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…et al, 2008, Figure 5I; Li et al, 2009, Figure 2G; Effendi et al, 2011, Figures 2A and 2B;Prasad et al, 2010, Figures 1A and 3). Even when both the data on primary root length and LR (and/or LRP) number or data on LR and LRP numbers are given (Swarup et al, 2008, Supplemental Figures 1D and 1E;Li et al, 2009, Figures 2F and 2G;Jiang et al, 2010, Figure 4B; Moreno-Risueno et al, 2010, Figure 4B; Ortiz-Castro et al, 2011, Figure 1E), one cannot explicitly understand whether a mutation or a treatment affects LR initiation when the data on LRP density and on the length of branching zone are not present.…”
Section: Are Numbers Of Lrs or Lrps Per Parent Root Useful Parameters?mentioning
confidence: 99%
“…Subsequent analysis showed that BRX mediates the interaction between brassinosteroids and auxin pathways, which is required for root growth (Mouchel et al, 2006). Later analysis suggested that BRX is also involved in cytokinin-mediated inhibition of LR development (Li et al, 2009) and furthermore, the auxin-cytokinin cross talk that coordinates cell division and differentiation in the root tip (Scacchi et al, 2010). Combining high-throughput confocal microscopy imaging, GWAS, and expression analysis, a then-uncharacterized gene encoding an F-box protein was found that underlies the natural variation of root development in a broad set of accessions (Meij贸n et al, 2014).…”
Section: Using Natural Variation To Identify Regulators Of Root Growtmentioning
confidence: 99%